2007
DOI: 10.1088/0957-4484/18/30/305301
|View full text |Cite
|
Sign up to set email alerts
|

Inherent-opening-controlled pattern formation in carbon nanotube arrays

Abstract: We have introduced inherent openings into densely packed carbon nanotube arrays to study self-organized pattern formation when the arrays undergo a wetting-dewetting treatment from nanotube tips. These inherent openings, made of circular or elongated hollows in nanotube mats, serve as dewetting centres, from where liquid recedes from. As the dewetting centres initiate dry zones and the dry zones expand, surrounding nanotubes are pulled away from the dewetting centres by liquid surface tension. Among short nano… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
9
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 16 publications
1
9
0
Order By: Relevance
“…Given the difficulty of dispersing and wetting CNTs in epoxy, capillaritydriven wetting of the aligned CNT forests is postulated as the underlying mechanism. Previous work with solvents has demonstrated a strong capillary effect of aligned CNT forests [24][25][26][27]. Our previous work with complex thermosets, including epoxies with similar viscosities as those used here, has demonstrated that long (exceeding 0.5 mm) aligned CNT forests are readily and effectively (i.e., no micron-scale voids) wet [14].…”
Section: Laminate Fabrication and Characterizationsupporting
confidence: 54%
“…Given the difficulty of dispersing and wetting CNTs in epoxy, capillaritydriven wetting of the aligned CNT forests is postulated as the underlying mechanism. Previous work with solvents has demonstrated a strong capillary effect of aligned CNT forests [24][25][26][27]. Our previous work with complex thermosets, including epoxies with similar viscosities as those used here, has demonstrated that long (exceeding 0.5 mm) aligned CNT forests are readily and effectively (i.e., no micron-scale voids) wet [14].…”
Section: Laminate Fabrication and Characterizationsupporting
confidence: 54%
“…Another problem of polymer nanocomposites formed using unaligned CNTs is that a uniform dispersion of CNTs leads to isotropic nanocomposite properties, which cannot be optimized for any single operating direction. These two shortcomings can be remedied by using aligned networks of CNTs, known as forests, where capillary forces can be used to aid with the polymer infusion, 19,[32][33][34] and where A-PNCs with anisotropic properties can be formed. Here the anisotropy in stiffness of variable V f A-PNCs formed via capillary-induced wetting is quantified, and their full three dimensional elastic constitutive relations are developed.…”
Section: 20mentioning
confidence: 99%
“…The matrix infuses into the CNT forest via capillary-induced wetting, at rates that depend on properties of the CNT forest (e.g., volume fraction) and the polymer (e.g., viscosity, contact angle). [32,33] The epoxy is cured following the recommended process for each polymer, yielding the desired nanocomposites (Fig. 1B).…”
mentioning
confidence: 99%
“…Several groups have investigated capillarity-induced wetting of CNT forests, focused on increasing the volume fraction of a dry CNT forest using solvent-induced densification, or creating controlled CNT micropatterns. [32,33,38,39] Low-viscosity and low-boiling-point solvents (e.g., isopropyl alcohol) are introduced into the ends of a CNT forest and because of capillary forces, the solvent is pulled into the forest and at the same time densifies it, creating a higher-volume-fraction A-CNT forest. The solvent-induced densification approach does not provide control over volume fraction, and the final densified forest is a function of the solvent and forest.…”
mentioning
confidence: 99%
See 1 more Smart Citation